Game-Based Learning as an Instructional Strategy for Enhancing Javanese Language Skills in Jepara Elementary Schools - Ludfiana, Rizka (Generate Digital Publishing, 2026)
Objective: This study aims to develop and implement a game-based learning (GBL) model to improve elementary school students’ proficiency in formal Javanese (Krama), by integrating local cultural contexts through the system of linguistic politeness. Research Design & Methods: This study employed a quantitative pre-experimental approach with a one-group pretest–posttest design involving elementary school students in Jepara. Research instruments included tests of Krama vocabulary mastery, understanding of speech levels, and speaking skills, as well as an observation sheet for student engagement. The intervention was conducted through collaborative and rapid-response games, accompanied by sentence translation activities and individual oral evaluations. Data were analyzed using descriptive statistics and a paired-sample t-test. Findings: The results showed consistent improvement across all aspects of Krama Javanese language proficiency, with average scores increasing from 59.2–61.8 (pretest) to 79.6–82.5 (posttest). The paired t-test confirmed a significant difference (t=8.022; df=11; p<0.001), thus proving that GBL is effective in improving vocabulary mastery, discourse comprehension, and speaking skills. Contributions: This study offers pedagogical and practical contributions to the development of an interactive, contextual, and student-centered regional language learning model, while also strengthening the integration of local cultural values into learning practices. Novelty: The novelty of this study lies in the integration of collaborative game elements with the cultural context of formal Javanese language usage within a quantitative pretest–posttest design that also considers student engagement as a factor contributing to the improvement of language proficiency.